2021
DOI: 10.1016/j.cca.2021.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Salivary SARS-CoV-2 antigen rapid detection: A prospective cohort study

Abstract: Background and aim SARS-CoV-2 quick testing is relevant for the containment of new pandemic waves. Antigen testing in self-collected saliva might be useful. We compared salivary and naso-pharyngeal swab (NPS) SARS-CoV-2 antigen detection by a rapid chemiluminescent assay (CLEIA) and two different point-of-care (POC) immunochromatographic assays, with that of molecular testing. Methods 234 patients were prospectively enrolled. Paired self-collected saliva (Salivette) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 28 publications
4
68
0
Order By: Relevance
“…Our results show a clear advantage of NPS as a specimen in combination with the probed antigen test. This is in concordance with other antigen test systems which, in general, have shown lower sensitivity compared to NPS [ 35 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. One of the automated antigen tests previously evaluated for saliva samples is the Lumipulse G SARS-CoV-2 Ag assay, a chemiluminescent enzyme immunoassay which received the CE marking for qualitative and quantitative detection of the SARS-CoV-2 N antigen on both saliva and NPS samples.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results show a clear advantage of NPS as a specimen in combination with the probed antigen test. This is in concordance with other antigen test systems which, in general, have shown lower sensitivity compared to NPS [ 35 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. One of the automated antigen tests previously evaluated for saliva samples is the Lumipulse G SARS-CoV-2 Ag assay, a chemiluminescent enzyme immunoassay which received the CE marking for qualitative and quantitative detection of the SARS-CoV-2 N antigen on both saliva and NPS samples.…”
Section: Discussionsupporting
confidence: 89%
“…A recent Cochrane study reported a sensitivity of only 56.2% (95% confidence interval (CI): 29.5–79.8%) for point-of-care antigen tests [ 33 ]. Several studies have evaluated saliva as an alternative to NPS for detection of SARS-CoV-2 with antigen tests, including automated tests [ 11 , 12 , 13 , 14 , 15 , 20 , 36 , 37 , 38 , 40 , 42 , 43 , 44 ]. However, none of the current Emergency Use Authorization (EUA) tests for SARS-CoV-2 antigen detection is authorized for saliva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this did not represent a major obstacle to achieve same day diagnostic definition, due to the timely organization and information flow. On the other hand, the disadvantage of longer process was overcome by the greater accuracy of a laboratory test compared to a POCT [2,9,10] and the ability to quickly perform the confirmation test with a system compatible with "urgent" execution.…”
mentioning
confidence: 99%